A governance and coordination perspective - Sweden's and Italy's approaches to implementing One Health - Sarah Humboldt-Dachroeden (Elsevier, 2022)
The aim of this study is to broaden the understanding of how different institutional and political contexts influence the successful implementation of One Health activities. To do this, a comparative case study of Italy and Sweden, based on qualitative interviews was conducted to get an inside perspective of the structural and operational factors that impacted the implementation of the One Health approach. Concretely, the study draws on thirty-one interviews of experts from Italian and Swedish public health, veterinary, food and environmental institutes that were conducted from 2020 to 2021.The study identified important differences and similarities across the two countries with respect to governance and coordination practices. The different governance practices demonstrated that the creation and design of government agencies affected the ability to collaborate within and across sectors. Another distinction among the countries was their different approach to One Health-related procedures and meetings. Non-formalised and irregular approaches lead to challenges for collaboration and more fragmented One Health-related outputs. Similar coordination approaches in the two countries showed that institutional and project-specific One Health strategies enabled an inclusive process of designing the One Health activities. Leaders can contribute to implementing One Health projects and networks, by brokering to different sectors, enabling heterophilious collaborations and promoting knowledge translation.Hence, the comparative analysis provided insights and lessons learned into understanding institutional and government set-ups influencing One Health implementation and can inform about processes and steps that are crucial when planning and designing One Health activities.